RESPON TANAMAN KEDELAI [Glycine max (L.) Merril] TERHADAP PEMBERIAN BIOCHAR DAN PUPUK NPK - Ferdinand, Ferdinand; Yulia, Arnis En; Isnaini, Isnaini (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2020)
The aim of this research was to examine the effect of biochar with the best NPK fertilizer that gives the best impact on the gr owth and productions of soybean. The experiment was conducted in an experimental field of Faculty of Agriculture, Riau University, in February until Juni 2019, the experimentallyusing factorial 4x2 conducted arranged completely randomized design (CRD) consist of four levels of biochar (control; 5 ton.ha-1 ;10 ton.ha-1;15 ton.ha-1) and two levels of NPK fertilizer (125 kg.ha-1;250 kg.ha-1). The data was analyzed of varience and further with the New Multiple Range Test (DNMRT) at the level of 5%. Parameters observed wereinternodes length, number of branch, flowering time, harvest time, the percentage of pithy pods of plant, crop seeed weight, productivity (g.m-2) and weight of 100 seeds. Result showed the application of biochar and NPK fertilizer has a significant effect on internodes length, number of branch, the percentage of pithy pods of plant, crop seeed weight, productivity (g.m-2). Interaction between 10 ton.ha-1 biochar at NPK 250 kg.ha-1 gave the best impact on the growth and productions of soybean. Keywords: Biochar, NPK fertilizer, Soybean.